The Epidemiology of Antibiotic-Related Adverse Events in the Treatment of Diabetic Foot Infections: A Narrative Review of the Literature - Laura Soldevila-Boixader; Oscar Murillo; Felix W. A. Waibel; Tanja Huber; Madlaina Schöni; Rahim Lalji; Ilker Uçkay (Antibiotics, 2023)
The use of antibiotics for the treatment of diabetic foot infections (DFIs) over an extended period of time has been shown to be associated with adverse events (AEs), whereas interactions with concomitant patient medications must also be considered. The objective of this narrative review was to summarize the most frequent and most severe AEs reported in prospective trials and observational studies at the global level in DFI. Gastrointestinal intolerances were the most frequent AEs, from 5% to 22% among all therapies; this was more common when prolonged antibiotic administration was combined with oral beta-lactam or clindamycin or a higher dose of tetracyclines. The proportion of symptomatic colitis due to Clostridium difficile was variable depending on the antibiotic used (0.5% to 8%). Noteworthy serious AEs included hepatotoxicity due to beta-lactams (5% to 17%) or quinolones (3%); cytopenia’s related to linezolid (5%) and beta-lactams (6%); nausea under rifampicin, and renal failure under cotrimoxazole. Skin rash was found to rarely occur and was commonly associated with the use of penicillins or cotrimoxazole. AEs from prolonged antibiotic use in patients with DFI are costly in terms of longer hospitalization or additional monitoring care and can trigger additional investigations. The best way to prevent AEs is to keep the duration of antibiotic treatment short and with the lowest dose clinically necessary.